A single to three phase power converter with integrated storage and a PV interface for rural power applications - Wolfs, Peter; Yang, F. (2014)
© 2014 IEEE. For economic reasons, many rural consumers are supplied from single phase medium voltage networks. Three phase power is desirable for many applications. This paper shows that a well-balanced three phase supply can be produced with a Scott transformer connection of a single phase inverter and the existing single phase supply. The single phase converter only processes half of the load power. A regulation scheme based in the DQ frame is proposed and it is shown the single phase inverter directly controls the quadrature axis voltage. A well balanced supply can be produced by regulating this inverter to eliminate any negative sequence voltages. A bidirectional rectifier supplies the inverter and simultaneously provides power factor correction and a reduced cost option to integrate storage and photovoltaic (PV) generation at its DC bus.